Pedalling analysis in BMX by telemetric collection of mechanic variables - Campillo, P.; Doremus, T.; Hespel, J.-M. (Brazilian Journal of Biomotricity, 2007)
The purpose of the study was to analyze the influence of crank lengths of the pedals on several kinematic and dynamic variables of pedaling. Nine national or international level subjects performed 3 series of 3 consecutive accelerations of 20 meters with 3 different crank lengths: 175, 180 and 182 mm. A telemetric acquisition system conceived and adapted specifically to an experimental BMX made it possible to collect the data of 2 dynamometers placed on the transmission crown and 2 velocity pick-ups fixed at the level of the teeth of the crown and the back hub. The results showed that on an acceleration phase of 20 m, linear velocities of the BMX equipped with cranks of 182 were significantly (P<0.001) higher Vb182 (6.8 ± 2.4 m/s) and Vb175 (5.8 ± 1.9 m/s). These results were the consequence of angular velocities significantly different in P<0.01 Omega182 (10.3 ± 4.3 rad/s) and Omega175 (9.4 ± 4.8 rad.s-1), which was not the case for the forces Fp175 (641.3 ± 190.6 N) and Fp182 (604.3 ± 210.9 N). These results allowed some of these sportsmen to reconsider the use of 182 mm cranks.